Digital Literacy Assistance for Senior Citizens: Bridging the Generational Tech Gap - Putrie, Rena Augia (Assoeltan: Indonesian Journal of Community Research and Engagement, 2025)
This community service initiative aimed to improve digital literacy among senior citizens, addressing the growing gap in technological access and usage that often marginalizes older adults in an increasingly digital world. The goal was to equip seniors with the necessary skills to navigate essential digital platforms for communication, healthcare, and daily activities. The service used a Participatory Action Research (PAR) approach, combining hands-on workshops with peer collaboration and continuous support. Participants engaged in practical tasks such as sending messages, making video calls, and accessing health services online. The results showed a significant improvement in participants' digital confidence, with many expressing increased autonomy and enhanced social connections. However, challenges such as limited access to devices and internet connectivity, along with physical impairments like poor eyesight and reduced dexterity, remained barriers. Despite these challenges, the program successfully fostered an environment of digital empowerment for senior citizens, demonstrating the positive impact of tailored digital literacy programs. In conclusion, this initiative highlights the importance of teaching technical skills and ensuring long-term access to technology for seniors. Future programs should address these barriers through partnerships and inclusive technology design to enhance the sustainability of digital literacy among older adults. This initiative contributes to the broader conversation on digital inclusion and empowerment, emphasizing the need for community-driven solutions to bridge the digital divide.